SAT0255 Regional variation in baseline patient characteristics and disease management of rheumatoid arthritis patients in the vigour (vioxx gi outcomes research) study. (1st June 2001) - Bombardier, C; Hochberg, M; Laine, L; Ramey, DR; Reicin, A; Watson, DJ
Abstract : Background: The VIGOUR Study was a large (n = 8076) randomised, double-blind, clinical trial comparing the GI safety of rofecoxib 50 mg. once daily to naproxen 500 mg twice daily. The median duration of follow-up was 9.0 months. Objectives: To describe the baseline patient characteristics and prior drug treatment by geographic region, for one of the largest cohorts of RA patients ever studied. Methods: We examined demographic characteristics, disease status, history of GI problems, and medication history for subgroups of patients from Europe (EUR, N = 1051); Latin America (LA, N = 2746); and North America (NA, N = 3795). Results: Baseline demographic characteristics were fairly comparable across regions. Most patients were female: 79% in EUR, 88% in LA, and 74% in NA. The respective mean ages were 58, 56, and 60 years, with 23%, 18%, and 32% over age 65. The participants had mean disease duration of 11, 10, and 11 years, and the majority of patients were in ARA functional class II (54%, 56%, 53%). In EUR, 70% were known to be seropositive with 81% in LA and 68% in NA. The proportions of patients known to have erosions on hand x-rays varied across regions (86%, 73%, 45%), as did the percentage with rheumatoid nodules (25%, 23%, 43%). The mean patient global disease activity scores were 2.2, 2.0, and 1.9 on a scale of 0–4, and mean investigator global disease activity scores were 2.1, 1.8, and 1.9 on a scale of 0–4. While the proportions of patients taking NSAIDs at baseline were similar (87%, 84%, 81%), the proportion taking corticosteroids in LA (72%) was much higher than in EUR (52%) and NA (46%). At baseline, patients had taken an average of 3.4, 2.8, and 3.0 DMARDs with the following proportions having ever taken individual medications in EUR, LA, and NA respectively: MTX: 70%, 76%, 71%; corticosteroids: 81%, 88%, 79%; hydroxychloroquine: 43%, 62%, 51%, injectable gold: 49%, 21%, 29%, sulfasalazine: 56%, 15%, 21%. The newest DMARDs had been used by only a handful of patients in EUR and LA; in NA, 4% had used etanercept and 7% had used leflunomide. 7%, 7%, and 9% of the patients reported a prior history of a GI ulcer or bleed at baseline, and 17%, 24%, and 20% reported dyspepsia within 14 days prior to baseline. 12%, 10%, and 14% had stopped an arthritis medication at some time due to abdominal pain. 28% of the LA patients had changed their arthritis medication in the previous year; compared to 50% in EUR and 46% in NA. Conclusion: Because of its size, the VIGOUR cohort is useful for studying regional differences in patient characteristics and treatment strategies. While most measured patient characteristics are similar, differences in the proportions of seropositive patients and patients with erosions and nodules may reflect other differences in the medical characteristics of the populations. This cohort also highlights differences in treatment strategies across regions as hydroxychloroquine was more frequently used in LA and injectable gold and sulfasalazine were more frequently used in EUR. The new DMARDs were being used more in the US, probably due to earlier regulatory agency approval.